A Islamic Law Analysis of the Pangkalan Balai Religious Court Decision Number 85/Pdt.G/2021/PA.Pkb Concerning the Pronouncement of Divorce (?al?q) to a Wife During Menstruation - Topan, M Apriansyah; Dewi, R.A Mariska; Yuliansyah, Yuliansyah; sulistiyo, Efendi; Mubarak, Syahrun (Yayasan Literasi Kita Indonesia, 2025)
Analysis of Islamic Law on the Decision of the Pangkalan Balai Religious Court Regarding the Pledge of Divorce to Wives in Menstruation Conditions. Marriage is an inner and outer bond between a man and a woman as husband and wife which aims to form a happy and eternal family based on God Almighty. Divorce is a form of breaking up a marriage. This happened in decision number 85/Pdt.G/2021/PA.Pkb which explained that there was a divorce on the grounds of one raj'i divorce. That at the time the petitioner made his declaration of divorce, the respondent was present at the trial and it was known that his condition was menstruating and he was prepared to pass the divorce. The judge informed that this case was included in the bid'i divorce. This study aims to explain how the decision process of the panel of judges regarding the pledge of divorce to the wife in a state of menstruation and to explain how the law of the pledge of divorce to the wife is in a state of menstruation at the Pangkalan Balai Religious Court decision number 85/Pdt.G/2021/PA.Pkb. This research is a field research (field research) with qualitative methods. There are two sources of data used, namely primary data sources, namely decision number 85/Pdt.G/2021/PA.Pkb and secondary data sources, namely the results of interviews with judges handling decisions number 85/Pdt.G/2021/PA.Pkb. Data collection techniques used are interviews, documentation, and literature. The data analysis technique used is a qualitative descriptive method that uses deductive conclusions. The result of this research is the bid'i divorce pledge process and is basically the same as the divorce pledge process in general. This is done because there is an agreement between husband and wife. Decision number 85/Pdt.G/2021/PA.Pkb is a bid'i divorce in Islamic law, its legal status is legal but its implementation is prohibited by Islam. In this case, the judges implement it according to the Qur'an at-talaq verse 1, it is haram if it is done.